2017
DOI: 10.1021/acs.macromol.6b01698
|View full text |Cite
|
Sign up to set email alerts
|

The PCPDTBT Family: Correlations between Chemical Structure, Polymorphism, and Device Performance

Abstract: We highlight the influence of processing conditions on polymorphism and structure formation on the mesoscale for the family of PCPDTBT polymers with branched alkyl side chains. Direct correlations of morphology to the chemical structure and to transistor device performance are established. We found that up to four different packing motifs could be realized depending on the polymer derivative and the processing conditions: amorphous, -stacked, cross-hatched and dimer-containing polymorphs. While C-and F-PCPDTBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 52 publications
5
65
0
Order By: Relevance
“…For comparison to C‐PCPDTBT, the thin film absorption spectra of Si‐PCPDTBT (M n = 11.0 kg mol ‐1 and PDI = 2.9) deposited from CHCl 3 and CB are shown in Figure b . While the overall shape of the spectra is similar to the carbon analogue, Si‐PCPDTBT shows regardless of solvent, a very pronounced aggregation shoulder at 760 nm . Our data indicate that the morphology (not shown) of Si‐PCPDTBT is much more dominated by aggregation in solution than in the case of C‐PCPDTBT.…”
Section: Third Generation Donor‐acceptor Copolymer: C‐pcpdtbtmentioning
confidence: 55%
See 2 more Smart Citations
“…For comparison to C‐PCPDTBT, the thin film absorption spectra of Si‐PCPDTBT (M n = 11.0 kg mol ‐1 and PDI = 2.9) deposited from CHCl 3 and CB are shown in Figure b . While the overall shape of the spectra is similar to the carbon analogue, Si‐PCPDTBT shows regardless of solvent, a very pronounced aggregation shoulder at 760 nm . Our data indicate that the morphology (not shown) of Si‐PCPDTBT is much more dominated by aggregation in solution than in the case of C‐PCPDTBT.…”
Section: Third Generation Donor‐acceptor Copolymer: C‐pcpdtbtmentioning
confidence: 55%
“…c) AFM height image of C‐PCPDTBT thin film spin coated from CB/DIO. d) Bilayer solar cell device architecture, e) field‐effect transistor device structure, f) J‐V curves of the solar cells and g) FET hole mobilities of the two polymorphs . Reproduced and adapted with permission .…”
Section: Third Generation Donor‐acceptor Copolymer: C‐pcpdtbtmentioning
confidence: 99%
See 1 more Smart Citation
“…These typically involve the steps of simulating realistic morphologies by molecular dynamics, partitioning into conjugation segments, calculating molecular charge transfer rates for pairs of conjugation segments and simulating the charge dynamics by master equation or kinetic Monte Carlo methods 75,76 . These methods were first applied to molecular systems such as discotic liquid crystals 77 , but have since also been shown to provide realistic estimates of carrier mobilities in conjugated polymers, including P3HT 78 , PBTTT 79,80 or the D-A copolymer PCPDTBT 81 . For PBTTT it was shown that the fluctuations in the transfer integrals (that is, dynamic disorder) occur mostly on timescales of <100 fs, which are faster than the timescale for charge transfer.…”
Section: Charge Transport In Low-disorder Conjugated Polymersmentioning
confidence: 99%
“…The structure of D‐A conjugated polymers is rather complex. Nanowires or nanofibers of several D‐A conjugated polymers had been reported . For example, Mullen et al prepared cyclopentadithiophene‐benzothiadiazole copolymer (CDT‐BTZ) nanowires by solvent vapor enhanced drop casting .…”
Section: Conjugated Polymer Single Crystals and Nanowiresmentioning
confidence: 99%